2015
DOI: 10.1016/j.jcin.2015.03.005
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombus Formation Following Transcatheter Aortic Valve Replacement

Abstract: These 4 cases elucidate the occurrence of valve thrombosis post-TAVR. Consideration should be given to treatment with dual antiplatelet therapy and oral anticoagulation in patients post-TAVR with increasing mean pressure gradients and maximum aortic valve velocity. Further research should be conducted to create guidelines for antithrombotic therapy following TAVR procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(103 citation statements)
references
References 28 publications
1
98
0
4
Order By: Relevance
“…The frequency of leaflet thrombosis, including symptomatic cases, varied widely from 0.19% to 40%. According to one case report, time of onset varies widely from 3 days to 2 years after procedure 13. When these literature references are combined, subclinical leaflet thrombosis seems to be observed 1–3 months after TAVI with the incidence up to about 10%–15% 14 15.…”
Section: Incidencementioning
confidence: 99%
“…The frequency of leaflet thrombosis, including symptomatic cases, varied widely from 0.19% to 40%. According to one case report, time of onset varies widely from 3 days to 2 years after procedure 13. When these literature references are combined, subclinical leaflet thrombosis seems to be observed 1–3 months after TAVI with the incidence up to about 10%–15% 14 15.…”
Section: Incidencementioning
confidence: 99%
“…Some studies found that patients undergoing TAVI had valve thrombosis, characterized by reduced leaflet motion, increased mean pressure gradients, and imaging abnormalities [13, 14, 36-38]. These studies demonstrated that oral anticoagulants have a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Some factors may be considered responsible for valve thrombosis, such as inadequate antiplatelet therapy, patients’ hypercoagulability, atrial fibrillation, endothelial injury produced by balloon predilation, and valve malposition, etc. [13, 36-38]. Thus, we should evaluate the condition of patients and their valve function to decide whether oral anticoagulants are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the relatively young era of percutaneous aortic valve replacement, an increasing number of reports has emerged describing cases of clinically relevant subacute post-TAVR valve thrombosis and recently identified reduced leaflet motion in MDCT, which may correspond to a subclinical surrogate of valve thrombosis [10,11,[23][24][25]. These reports about post-TAVR valve thrombosis and hindered leaflet function have generated debate about the clinical relevance of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%